Characterization of Face-Selective Patches in Orbitofrontal Cortex - Troiani, Vanessa; Dougherty, Chase C.; Michael, Andrew M.; Olson, Ingrid R. (Frontiers in Human Neuroscience, 2016)
Social animals are naturally drawn towards conspecifics: from birth onwards we orient towards other humans and we seek social interactions. In this paper we tested the hypothesis that a region in the orbitofrontal cortex (OFC), previously identified by electrophysiology and fMRI studies in non-human primates, is preferentially sensitive to faces due to their socially rewarding properties. Twenty healthy college students were scanned while viewing several categories of stimuli including social rewards (faces) and non-social rewards (appetizing foods). In addition, social motivation was measured with the Broader Autism Phenotype Questionnaire (BAP-Q). Results show that face-selective patches can be identified at the individual level and in the majority of participants. Medial portions of the OFC were face-selective, and activity in this region scaled individual differences in social motivation. In contrast, lateral portions of the OFC were responsive to faces and foods, indicating a domain-general value response in lateral OFC. Analysis of resting state scans showed positive functional connectivity between the amygdala, anterior temporal face patches, and medial OFC, regions that are linked by the a white matter tract called the uncinate fasciculus. These findings have implications for research on social motivation, which is highly relevant to understanding deficits in autism spectrum disorder.